Understanding Whence We Came: Role of the Association for Communication Excellence in the Development of Agricultural Communications during the Past Century - and Future Implications - D. Dwayne Cartmell II; James F. Evans (Journal of Applied Communications, 2013)
Role of the Association for Communication Excellence in the Development of Agricultural Communications during the Past Century - and Future Implications.
Keywords: Understanding; Whence; Agricultural Communications; Natural Resources; Future Implications